Acute Effects of 30 g Cyclodextrin Intake during CrossFit® Training on Performance and Fatigue - Franscisco Javier Grijota; Víctor Toro-Román; Ignacio Bartolomé; Elías Cordero-Román; Cristian Sánchez López; Jose Miguel Jiménez; Ismael Martínez-Guardado (Journal of Functional Morphology and Kinesiology, 2024)
The main objective of this study was to investigate the influence of carbohydrate intake (cyclodextrin) on performance during the performance of two consecutive workouts of the day (WODs) lasting 20 min each. Twenty-one male CrossFit (CF) athletes (29.5 ± 4.3 years; 72.81 ± 12.85 kg; 1.74 ± 0.06 m; 3.41 ± 1.21 years of experiences) participated in a crossover, randomized, and double-blind study. The effect of supplementation with 30 g of cyclodextrin (SG) (Cluster Dextrin®) or placebo (PG) (Bolero Advanced Hydration®) was evaluated on the performance of two specific WOD. Additionally, the effect on handgrip maximum strength, countermovement jump (CMJ), Wingate test, and 1 RM bench press test was evaluated. The effect on blood glucose and lactate was also evaluated. No differences were found in time, height, and power (W/Kg) in CMJ. However, there was a percentage improvement in CMJ jump power (W) (p < 0.05) between the groups, assuming an improvement in performance due to the intervention. Moreover, both conditions experimented differences in execution speed between sets (p < 0.05) in pre-WOD, and differences in post-WOD only in the placebo group, as well as decreases in this variable per repetition across the set (p < 0.01) in both conditions. However, no differences were found in the rest of the variables. Supplementation with 30 g of cyclodextrin did not have any metabolic or performance effects in CF tests. Although some differences between groups were observed in CMJ and power tests for bench press, the data are not conclusive and further research is needed in this regard.